PEMANFAATAN MEDIA SABUT KELAPA MELALUI PROJECT BASED LEARNING DAN DISCOVERY lEARNING UNTUK MENINGKATKAN MOTORIK HALUS DAN KEMANDIRIAN ANAK USIA DINI - Zulfa Fardhinah; Mau Izhatun Syarifah; Anisa Mutia Sari; Celia Cinantya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low levels of learning engagement, fine motor skills, and independence were identified among children in Group B2 at TK Terpadu Negeri Pembina Banjarmasin Tengah. This study aimed to improve these developmental aspects through the implementation of Project Based Learning integrated with Discovery Learning using coconut husk as a natur al learning material. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles involving 18 children. Data were collected through observation, performance assessment, and documentation and analyzed using descriptive qualitative and quantitative techniques. The findings revealed that children's learning engagement increased from 33.3% in the pre-cycle to 66.7% in Cycle I and 88.9% in Cycle II. Fine motor skills improved from 44.4% to 77.8%, reaching 88.9% in the second cycle. Children's independence also increased from 38.9% to 72.2%, and finally reached 94.4% in Cycle II. These findings indicate that integrating Project Based Learning with Discovery Learning using coconut husk as a natural learning material effectively promotes active, contextual, and meaningful learning while enhancing young children's developmental outcomes.